Evaluating inter-local government cooperation and governance in the Philippines: The case of the MNDC, the MMDA, and the Metro BLIST - Datoon, Rodmyr F. (Animo Repository, 2009)
Local governance in the country is constantly changing since the passage of the Local Government Code. Inter-local government cooperation (ILGC) is an innovative form of local governance which is being adopted by an increasing number of local government units in the urban and rural areas of the country. Entering into an ILGC may help the local government units to enhance their service provision through economies of scale improved their planning and governance by pooling and complementing their resources resolve cross-boundary problems and address their shared local problems together. Different forms of inter-local government cooperation may display unique characteristics in terms of scope and nature and in terms of the services and programs that they provide. One thing that is constant is that these arrangements are about relationships between political entities and its creation and functions involve political processes among LGUs, national officials and different local stakeholders. ILGC in the country, however, is still in its infant stages of development. There is still much to learn about the motives and the factors that are involved in the creation and function of such kind of governmental arrangement. Furthermore, it is yet to learn how ILGC relates to other form of governments such as the LGUs, provincial governments, and the national government. This study has looked at the cases of Metro Naga Development Council, the Metro Manila Development Authority and the BLIST. It focused on the description of the creation of ILGC and how it performs its services and programs. This study is also concerned in identifying the different motives and factors that may enable or constrain the ILGC. Based on the cases examined, ILGC is created to address the common needs of the LGUs. The cases also highlighted the important roles of leadership, enabling laws, national government support, and the sense of ownership, in the creation and functions of the 3 ILGC cases.